Cissie Fairchilds, Women in early modern Europe, 1500—1700 - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2010)
Cissie Fairchilds offers a comprehensive synthesis of the main categories associated withgender history in early modern Europe. In particular, she draws attention to the uneasy relationship between patriarchal theory and the real lived experience of women who negotiatedand subverted masculine worlds during their everyday social interactions. Fairchilds has notintended this book to be a work of original research, but a textbook to present and reflectupon the major themes of gender history over the last few decades. As such, it is written in anengaging and accessible style, with clearly defined sections enabling the reader to understandthe aims and intent of each part, as well as leaving him or her with a sound general introduction to gender history.